Linear and nonlinear optical properties of 3-nitroaniline (m-NA) and 4-nitroaniline (p-NA) crystals: A DFT/TDDFT study. (October 2015) - Dadsetani, M.; Omidi, A.R.
Abstract: We have studied the electronic structure and optical responses of 3-nitroaniline and 4-nitroaniline crystals within the framework of density functional theory (DFT). In addition, the excitonic effects are investigated by using the recently published bootstrap exchange-correlation kernel within the time dependent density functional theory (TDDFT) framework. Our calculations based on mBJ approximation yield the indirect band gap for both crystals, but the larger one for m-NA. Due to the excitonic effects, the TDDFT calculations gives rise to the enhanced and red-shifted spectra (compared to RPA). Due to the weak intermolecular interactions, band-structure calculations yield bands with low dispersion for both crystals. This study shows that the substituent groups play an important role in the top of valence band and the bottom of conduction band. Due to the linear structure of p-NA molecule, the highest peaks are located in the optical spectra of p-NA crystal, while m-NA has more sharp peaks, especially at lower energies. Both DFT and TDDFT calculations for the energy loss spectra show plasmon peaks around 27 and 28 eV for p-NA and m-NA, respectively. Due to the non-centrosymmetric structure of m-NA crystal, we also have reported its nonlinear spectra and the 2 ω / ω intra-band and inter-band contributions to the dominant susceptibilities. Findings indicate the opposite signs for these contributions, especially at higher energies. The comparison between nonlinear spectra and the linear spectra (as a function of both ω and 2 ω ) reveals the significant resemblance between linear and nonlinear patterns. In addition to the reasonable agreement between our results with experimental data, this study reveals the spectral similarities between crystalline susceptibility and molecular polarizability. Highlights: Due to the low intermolecular interactions, the p-NA and m-NA crystals have band structures with low dispersions. The m-NA crystal is a good candidate for SHG, but p-NA is not. The p-NA crystal show smaller band gap, higher dielectric response and much better anisotropy compared to m-NA. So it can be a suitable crystal for higher order nonlinear responses. Both crystals have enough small wavelengths of Plasmon peaks. So they can be useful in Plasmon-based technology. The excitonic effects can change the optical properties of m-NA and p-NA crystals, especially near the band edge.